2020
DOI: 10.1007/s00204-020-02691-9
|View full text |Cite
|
Sign up to set email alerts
|

Robustness testing and optimization of an adverse outcome pathway on cholestatic liver injury

Abstract: Adverse outcome pathways (AOPs) have been recently introduced as tools to map the mechanisms underlying toxic events relevant for chemical risk assessment. AOPs particularly depict the linkage between a molecular initiating event and an adverse outcome through a number of intermediate key events. An AOP has been previously introduced for cholestatic liver injury. The objective of this study was to test the robustness of this AOP for different types of cholestatic insult and the in vitro to in vivo extrapolatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 69 publications
7
45
1
Order By: Relevance
“…The presence of the concentrated mix of BAs in the in vitro system creates an environment more comparable to the in vivo situation, since cholestasis patients present with 30-50× increased concentrations of serum BA [21,56,57]. The addition of BAs seems to potentiate the effect of cholestatic drugs [31]. The sensitizing effect of BAs was also observed for Cx26, as mRNA levels were reduced following exposure of the human hepatoma HepaRG cells to cholestatic drugs and BAs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The presence of the concentrated mix of BAs in the in vitro system creates an environment more comparable to the in vivo situation, since cholestasis patients present with 30-50× increased concentrations of serum BA [21,56,57]. The addition of BAs seems to potentiate the effect of cholestatic drugs [31]. The sensitizing effect of BAs was also observed for Cx26, as mRNA levels were reduced following exposure of the human hepatoma HepaRG cells to cholestatic drugs and BAs.…”
Section: Discussionmentioning
confidence: 98%
“…In general, the outcome of cholestasis on Cx43 in vitro seems to depend on the nature of the drug. In this light, three triggering factors of DIC have been identified, namely transporter changes, hepatocellular changes and altered bile canaliculi dynamics [31], where all are differentially affected by ATV, CsA and NEF. These triggering factors result in BA accumulation, which in turn induces two cellular responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is critical in view of appropriate application. In this context, a recent study showed that the only available AOP on cholestatic liver injury seems fit to model the intrahepatic type of cholestasis, but less for the extrahepatic counterpart [23]. This suggests that more than one AOP is required to mechanistically describe a liver disorder with different etiology.…”
Section: Future Perspectives: Technical Optimization and Interdisciplmentioning
confidence: 99%
“…This means that the evidence was collected from heterogeneous sources in the scientific literature. Such studies were not designed originally to support building an AOP, and there are only very few recent examples of AOPs that are based on dedicated research to build the AOP and to parameterize KERs (Browne et al 2015(Browne et al , 2017Gijbels et al 2020;Pistollato et al 2020;Spinu et al 2019).…”
Section: Introductionmentioning
confidence: 99%